Perilaku Menyontek Sebagai Bentuk Perilaku Bermasalah: Analisis Faktor dan Strategi Deteksi Dini - Olivia Maharani; Ajeng Chandra Prameswari; Risma Anita Puriani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
In the field of education, cheating remains a critical issue of academic dishonesty. This phenomenon does not merely affect students' grades but also obstructs the development of core character values, including integrity, responsibility, and independence in the pursuit of knowledge. This article aims to analyze the factors influencing cheating behavior and evaluate various forms of intervention from the perspective of early detection of problematic behavior. This study employs a literature review method, examining 20 relevant scientific articles published between 2021 and 2026. The findings reveal that cheating behavior is influenced by internal factors such as self-efficacy, self-control, self-confidence, religiosity, and self-esteem as well as external factors, including peer conformity, parental pressure, the learning environment, and evaluation systems. Effective interventions include group counseling services, classical guidance, modifications to evaluation systems, and the utilization of Artificial Intelligence-based technology to detect potential academic fraud. Consequently, efforts to prevent cheating behavior require a multidimensional approach involving students, teachers, parents, and school policies to cultivate an academic culture of integrity.